Re: Videnros C, Selander J, Wiebert P, Albin M, Plato N, Borgquist S, Manjer J, Gustavsson P. Postmenopausal breast cancer and occupational exposure to chemicals. Scand J Work Environ Health. 2019;45(6):642–650. doi:10.5271/sjweh.3822 - Videnros, Cecilia (Scandinavian Journal of Work, Environment & Health, 2022)
This erratum concerns the methods section. The error relates to the adjustment for physical activity, which was made for physical activity outside of work, not for physical activity at work, as erroneously stated on page 644.